Dental Tissue and Stem Cells Revisited: New Insights From the Expression of Fibroblast Activation Protein-Alpha - Driesen, Ronald B.; Hilkens, Petra; Smisdom, Nick; Vangansewinkel, Tim; Dillen, Yörg; Ratajczak, Jessica; Wolfs, Esther; Gervois, Pascal; Ameloot, Marcel; Bronckaers, Annelies; Lambrichts, Ivo (Frontiers in Cell and Developmental Biology, 2020)
Fibroblast activation protein-α (FAPα) is a membrane protein with dipeptidyl-peptidase and type I collagenase activity and is expressed during fetal growth. At the age of adolescence, FAPα expression is greatly reduced, only emerging in pathologies associated with extracellular matrix remodeling. We determined whether FAPα is expressed in human dental tissue involved in root maturation i.e. dental follicle and apical papilla and in dental pulp tissue. The dental follicle revealed a high concentration of FAPα and vimentin-positive cells within the stromal tissue. A similar observation was made in cell culture and FACS analysis confirmed these as dental follicle stem cells. Within the remnants of the Hertwigs’ epithelial root sheath, we observed FAPα staining in the E-cadherin positive and vimentin-negative epithelial islands. FAPα- and vimentin-positive cells were encountered at the periphery of the islands suggesting an epithelial mesenchymal transition process. Analysis of the apical papilla revealed two novel histological regions; the periphery with dense and parallel aligned collagen type I defined as cortex fibrosa and the inner stromal tissue composed of less compacted collagen defined as medulla. FAPα expression was highly present within the medulla suggesting a role in extracellular matrix remodeling. Dental pulp tissue uncovered a heterogeneous FAPα staining but strong staining was noted within odontoblasts. In vitro studies confirmed the presence of FAPα expression in stem cells of the apical papilla and dental pulp. This study identified the expression of FAPα expression in dental stem cells which could open new perspectives in understanding dental root maturation and odontoblast function.